A mega project analysis : Sapura Telecommunications Berhad / Anizah Othman, Nor Julia Ahmad and Sumi Suriamorni Ismail - Othman, Anizah; Ahmad, Nor Julia; Ismail, Sumi Suriamorni (Faculty of Business and Management, 2000)
Sapura is presently in three main business areas such as Telecommunications, Information Technology, Metal-Based Industries as well as the continued towards Research and Development. In addition to make their company expand into the worldwide, they were setting their sights on New Global Markets. While by consolidating their activities in the IT focused in Industry, they also plan to diversify into a range of businesses which meet specialized requirements and projects. Sapura Telecommunications also have started venturing into property management and building maintenance, construction and the tourism business. Sapura facing some competitors in telecommunication industry where most of them compete each other to gain competitive advantages and expand business worldwide. Some of competitors consist of DiGi Com. Berhad, Maxis Berhad, Telekom Berhad, Celcom Berhad and also Mobikom Berhad. Each companies has their own strengths in order to attract customers in this industry. Start in year 1997, Sapura facing problems in maintaining their performance of generating sales and revenue as we can see in their financial ratio, most of ratio is indicate bad performance. This may due from economic downturn that faced by our country. In order to established back their market and business, sapura should change some strategies in order to maintain and expand more in industry. Base on analysis, the appropriate strategies that can be taken are market penetration and product development. As consequences from high demand in telecommunication industry and increasing in population, Sapura should develop more on this strategies. As a conclusion, now Sapura become one of the most popular distributors telecommunication products in Malaysia. They acquired more established IT companies in order to compete with the competitors in global market. Futhermore, the decreasing in performance in a year 1997 until 1999 due to recession in our country. As overall, Sapura can be a developed companies in telecommunication industry as they have many strengths and opportunities to gain.